Efterpi Mitsi, Greece in Early English Travel Writing, 1596–1682 - Sell, Jonathan Patrick Alan (Historein, 2022)
Review of Efterpi Mitsi. Greece in Early English Travel Writing, 1596–1682. Basingstoke: Palgrave Macmillan, 2017. 206 pp.